2022
DOI: 10.3389/feart.2022.823286
|View full text |Cite
|
Sign up to set email alerts
|

Future Changes of Summer Heat Waves Over Urban Agglomerations in Eastern China Under 1.5°C and 2.0°C Global Warming

Abstract: Extreme hot events have increased evidently under global warming, particularly in the urban areas. This study aims to explore the detailed features of future changes in summer heat waves (HWs) over three major urban agglomerations (Beijing Tianjin Hebei, BTH; Yangtze River Delta, YRD; Pearl River Delta, PRD) in eastern China under 1.5 and 2.0°C warming scenario by using the Weather Research and Forecasting model (WRF) with the updated land cover data for China (ChinaLC), which is also coupled with urban canopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Ma et al [17] studied the extreme temperatures in Northern China and pointed out that the change in extreme temperatures is closely related to regional warming; they concluded that since the 1990s, the frequency of the highest temperature in most parts of Northern China has increased significantly. Ma et al [18] discussed and studied the detailed characteristics of the future changes in summer heat waves over three major urban agglomerations (Beijing-Tianjin-Hebei (BTH) region; the Yangtze River Delta (YRD); the Pearl River Delta (PRD)) in Eastern China under the 1.5 and 2.0 • C warming scenarios, and they found that the predicted change in the heat wave index in urban areas is much higher than that in non-urban areas, which means that urban areas will face higher heat-related disease or environmental risks than suburban or rural areas in the future. In addition, studies on the spatiotemporal characteristics of extreme heat events in the Yellow River Basin [19], the Huaihai Basin [20], the Qinghai-Tibet Plateau [21], and other regions showed that the change in extreme temperature will lead to regional climate change and be affected by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [17] studied the extreme temperatures in Northern China and pointed out that the change in extreme temperatures is closely related to regional warming; they concluded that since the 1990s, the frequency of the highest temperature in most parts of Northern China has increased significantly. Ma et al [18] discussed and studied the detailed characteristics of the future changes in summer heat waves over three major urban agglomerations (Beijing-Tianjin-Hebei (BTH) region; the Yangtze River Delta (YRD); the Pearl River Delta (PRD)) in Eastern China under the 1.5 and 2.0 • C warming scenarios, and they found that the predicted change in the heat wave index in urban areas is much higher than that in non-urban areas, which means that urban areas will face higher heat-related disease or environmental risks than suburban or rural areas in the future. In addition, studies on the spatiotemporal characteristics of extreme heat events in the Yellow River Basin [19], the Huaihai Basin [20], the Qinghai-Tibet Plateau [21], and other regions showed that the change in extreme temperature will lead to regional climate change and be affected by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the start of the new millennium, the world has witnessed a drastic increase in the impacts and rates of natural hazards attributed to climate change and accelerated urbanization. During the past twenty years, the world has witnessed several devastating natural disasters that have brought far greater damage than in previous years; this trend is set to increase due to global warming, climate change, and rapid urbanization (Salimi and Al-Ghamdi, 2020;Tahir et al, 2021;Chen et al, 2022;Ma et al, 2022). The impact of climate change on the world includes a wide spectrum of natural disasters, such as unusual precipitation (in arid areas) and unusual extreme heatwaves, accompanied by record-breaking high temperatures (Tahir et al, 2021), (Attia et al, 2021), (García-Herrera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%